Landscape metrics to analyze the forest fragmentation of Chitteri Hills in Eastern Ghats, Tamil Nadu - Narmada K; Dipjyoti Gogoi; Dhanusree; Bhaskaran G (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2021)
Chitteri Hills of Eastern Ghats is primarily covered by evergreen forests and deciduous forests. Forest Management, change in landuse and rapid economic development has caused a minor change in the landscape of Chitteri. In the current study the forest fragmentation was assessed using the Fragstat 4.0 software for different classes using specific metrics. Fragstats 4.0 spatial pattern analysis was applied for different landuse classes that was derived from landuse and landcover maps prepared using the Landsat 8 digital data. The results from the above analysis have shown that there was more fragmentation in the Chitteri Hills. Class Area (CA), Percentage of Landscape (PLAND), Largest Patch Index (LPI), Number of Patches (NP), Patch Density (PD), Area Weighted Mean Shape Index (AWMSI) at the class level was quantified in the present study. These spatial metrics were found to be very simple and helpful in quantification of the complex spatial processes and can be used as an effective means for monitoring the Chitteri Landscape.